Glorious greetings - Twelvetrees, Kate (Quarto Book, 1996)
A collection of 100 designs for creating greeting cards. It covers a variety of styles and techniques, from embroidery and patchwork to papier mache, collage and pop-ups. Illustrations and step-by-step instructions are provided, along with ideas on how to present and protect the cards.